Maqamat Sufi dan Tafsir Alquran: (Kajian Tafsir Sufi Imam Al-Qusyairi dengan Teori Hierarki Makna Abdullah Saeed) - Wathani, Syamsul; Muluk, Tajul (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
”The history of Qur’anic Exegesis shows that there is a pattern of interpretation of the Qur’an that originates not only from reasoning (ta’aqquli), but also from spiritual emanations (at’ta’ammul ad-diniyyah). The importance of understanding the exegetical patterns/models driven by the Sufis, in order to become a better alternative to the patterns of understanding/interpreting the Qur’an. This article will conduct an analysis with a focus on: Sufi interpretation; scientific analysis and religious appreciation, discourse of meaning in Sufi interpretation, and patterns/models of al-Qusyairi’s Sufistism interpretation. The research framework used is Abdullah Saeed’s hierarchy of values to read the hierarchy of meaning of the Sufi al-Qusyairi interpretation. The findings of this research include: Sufi interpretation is a tafir based on knowledge (knowledge) and the depth of Islamic charity (experience). Al-Qusyair Sufi interpretation is elaborates between knowledge and Islamic spiritual experience. In the discourse of meaning, Sufi interpretation is based on the condition of the Sufi soul at different states (ahwal) and spiritual levels (maqamat). However, mystical perception of the Qur’an must come to terms with its birth meaning. The Sufistic interpretation of al-Qusyairi can combine the meaning of isyariyyah with the meaning of lahiriah verse. Al-Qusyairi understands that the contents of the Koran have three levels of meaning according to the level of maqa>m in the concept of tasawwuf, namely: ’irfani, burhani and bayani.